Evaluation of the linear measurements by conventional radiographs and indirect digital images in the endodontic treatment (Journal of Applied Oral Science, 2004)
INTRODUCTION: A successful endodontic therapy depends on the linear measurements obtained by means of radiographs taken during odontometry and also on the application of the established working length up to the final obturation. OBJECTIVE: The aim of this study was to compare the precision of the linear measurement obtained by means of conventional radiographs and indirect digital images evaluated by the Digora 1.5 software during the different stages of endodontic treatment, as well as to evaluate the tools available on this software. METHODS: A total of 160 radiographs of single-rooted teeth were obtained from files, which were analysed and divided in 4 groups comprising odontometry, cone fit, condensation and the final obturation. Analyses of the conventional radiographs and digitized images were performed by five previuosly calibrated examiners. RESULTS: A high level of inter and intra-examiner agreement was observed through application of the Kendall coefficient and the correlation index, respectively. In relation to the results of linear measurement, the two-way variance analyses and the Tukey test revealed that, concerning the method, a statistically significant decrease was observed on the measurement obtained through the digital method when compared to the conventional radiograph (p